Comparative Study of Islamic Religious Education (PAI) Leraning Management at Elementary School - Lisawati Lisawati (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2020)
Islamic religious education learning at each educational institution has a different management pattern even though at one level within the education unit level, differences in management need to be disclosed as an effort to obtain information related to the strengths and weaknesses of each institution, related to this, this study aimed to find out the management of Islamic religious education carried out by teachers at two public elementary schools. From the data analysis conducted, Islamic religious education management at SD Negeri 02 and 13 Petok Pasaman are: 1) Islamic teachers carry out various preparations and designs before implementing learning, the preparation of learning plans was carried out through studies of various aspects related to learning. 2) the learning implementation by the teachers of SDN 02 was quite creative and innovative, in contrast to the Islamic religious education at SD Negeri 13 which still relies on conventional aspects of learning methods and media. 3)Islamic teacher of SD Negeri 02 Petok conducted a conceptual, structured, and systematic learning evaluation.